Promosi Kesehatan Terintegrasi Berbasis Fase Operasional Haji dalam Upaya Pencegahan Dehidrasi dan Heat-Related Illness pada Jemaah Haji Indonesia di Makkah - Yan Cahyadi Anas; Mahendro Prasetyo Kusumo (Jurnal Medika: Medika, 2026)
Alibigloo, H. P., & Eshaghi, Z. (2025). The Integrated Model of Health Behavior Promotion (IMHBP): A Synergistic Approach to Promote Health-Oriented Behaviors. The Open Public Health Journal, 18(1). https://doi.org/10.2174/0118749445375249250206112941 Amalia, F., Maya Savitri, P., Agustini, D. P., Kristanti, M., Studi Kedokteran Sarjana, P., Kedokteran, F., Pembangunan Nasional, U., & Ilmu Kesehatan Matra, D. (2025). Hubungan Pengetahuan Dengan Sikap Pada Calon Jemaah Haji dan Umrah Lansia Terhadap Pencegahan Dehidrasi. Journal Of The Indonesian Medical Association, 75(5), 220–225.   https://doi.org/10.47830/JINMA-VOL.75.5-2025-1859 Efe, H., & Umdu Topsakal, Ü. (2025). Public Opinion Study on School Health Education Programs: Family Needs Assessment Study. International Journal of Environmental Research and Public Health 2025, Vol. 22, Page 1088, 22(7), 1088. https://doi.org/10.3390/IJERPH22071088 Goes, A. R. (2025). Advocacy for Health and Health Equity: A Call to Public Health Professionals. Portuguese Journal of Public Health, 43(1), 1. https://doi.org/10.1159/000545038 Goni, M. D., Naing, N. N., Hasan, H., Wan-Arfah, N., Deris, Z. Z., Arifin, W. N., Baaba, A. A., Adam, B. M., & Arshad, M. R. (2021). Effectiveness of a Novel Smartphone Health Education Intervention in Enhancing Knowledge, Attitudes, and Practices for the Prevention of Respiratory Tract Infections Among Private Hajj Pilgrims From Malaysia. Frontiers in Public Health, 9, 594204. https://doi.org/10.3389/FPUBH.2021.594204 Hietbrink, E. A. G., Lansink, C., Laverman, G. D., Vollenbroek-Hutten, M. M. R., Middelweerd, A., & Tabak, M. (2025). Systematic review of dynamically tailored eHealth interventions targeting physical activity and healthy diet in chronic disease. NPJ Digital Medicine, 8(1). https://doi.org/10.1038/S41746-025-02054-7 Koh, A., Swanepoel, D. W., Ling, A., Ho, B. L., Tan, S. Y., & Lim, J. (2021). Digital health promotion: promise and peril. Health Promotion International, 36(Suppl 1), i70. https://doi.org/10.1093/HEAPRO/DAAB134 Moran, M. B., Frank, L. B., Chatterjee, J. S., Murphy, S. T., & Baezconde-Garbanati, L. (2016). Information scanning and vaccine safety concerns among African American, Mexican American, and non-Hispanic White women. Patient Education and Counseling, 99(1), 147–153. https://doi.org/10.1016/J.PEC.2015.08.016 Samarkandi, O., Alamri, F., Alsaleh, G., Al Abdullatif, L., Alhazmi, J., Basnawi, M., Alazmy, W., & Khan, A. (2025). Exploring the prevalence of chronic diseases and health status among international Hajj pilgrims. PLoS ONE, 20(4 April). https://doi.org/10.1371/JOURNAL.PONE.0317555 Turin, T. C., Chowdhury, N., Haque, S., Rumana, N., Rahman, N., & Lasker, M. A. A. (2021). Meaningful and deep community engagement efforts for pragmatic research and beyond: engaging with an immigrant/racialised community on equitable access to care. BMJ Global Health, 6(8). https://doi.org/10.1136/BMJGH-2021-006370 van der Vliet, N., Suijkerbuijk, A. W. M., de Blaeij, A. T., Ardine de Wit, G., van Gils, P. F., Staatsen, B. A. M., Maas, R., & Polder, J. J. (2020). Ranking Preventive Interventions from Different Policy Domains: What Are the Most Cost-Effective Ways to Improve Public Health? International Journal of Environmental Research and Public Health, 17(6). https://doi.org/10.3390/IJERPH17062160 Yezli, S., Ehaideb, S., Yassin, Y., Alotaibi, B., & Bouchama, A. (2024a). Escalating climate-related health risks for Hajj pilgrims to Mecca. Journal of Travel Medicine, 31(4). https://doi.org/10.1093/JTM/TAAE042 Yezli, S., Ehaideb, S., Yassin, Y., Alotaibi, B., & Bouchama, A. (2024b). Escalating climate-related health risks for Hajj pilgrims to Mecca. Journal of Travel Medicine, 31(4), taae042. https://doi.org/10.1093/JTM/TAAE042 33-41.